Hubungan Rasio Neutrofil Limfosit terhadap Komplikasi Kardiovaskular pada Pasien Penyakit Ginjal Kronik Hemodialisis - Akmal, Thariq Hikmatul; Susanto, Agung; Dewi, Ratih Tri Kusuma; Sunggoro, Agus Jati (Jurnal Penyakit Dalam Indonesia, 2024)
Introduction. The neutrophil-to-lymphocyte ratio (NLR) is a simple parameter to assess the inflammatory status, especially in chronic kidney disease (CKD) patients experiencing capillary damage due to increased glomerular capillary pressure. In a state of vascular endothelial inflammation, there is a higher tendency to form atherosclerotic plaques and calcification that can induce cardiovascular events such as heart failure, coronary heart disease, and stroke. This study aimed to determine the relationship between the NLR and cardiovascular complications in CKD patients undergoing hemodialysis. Methods. An analytical observational study with cross-sectional approach was conducted among 119 CKD patients undergoing hemodialysis at Dr Moewardi Regional Hospital who met the inclusion and exclusion criteria. The relationship between the two variables was analyzed using Fisher exact test. Results. The majority of subjects in this study were male (51.3%) and were aged over 50 years old (63.9%). Most subjects experienced complications of heart failure (54.6%), followed by coronary heart disease (19.3%), and stroke (17.7%). Analysis of complete blood count data showed a mean neutrophil count of 77.20% (SD 11.49), lymphocytes 13.64% (SD 8.23), and NLR 10.7 (SD 10.3). Notably, a majority of participants exhibited an NLR value ≥3.5, observed in 95 individuals (79.8%). Fisher exact test results indicated a significant relationship between elevated NLR and cardiovascular complications in hemodialysis CKD patients (p-value= 0.028). Conclusion. There is a significant relationship between NLR and cardiovascular complications in CKD patients undergoing hemodialysis.